The relationship between informational justice and affective commitment: The Mediating effect of transactional leadership - Ghazali, Jafni; Wahab, Samsudin; Khalid, Nor Aminin; Jafni, Nurul Huda; Mohd Saderi, Shahrizal (Journal of Islamic, Social, Economics and Development, 2025)
This study examines the connection between informational justice, affective commitment, and transactional leadership at Maktab Rendah Sains MARA, focusing on how transactional leadership serves as a mediating variable. Informational justice pertains to the quality, transparency, and adequacy of information leaders share, essential for enhancing organizational outcomes. The research highlights issues like inconsistent communication and lack of feedback that undermine organizational effectiveness and commitment. The study uses a quantitative approach to test a conceptual framework with data collected from an online questionnaire involving 463 MRSM leaders. A stratified random sample of 210 respondents from diverse job positions was analyzed. The results indicate that transactional leadership partially mediates the relationship between informational justice and affective commitment, suggesting that effective transactional leadership can strengthen the positive impact of perceived fairness in information sharing on emotional attachment to the organization. This highlights the importance of communication strategies leaders use to commit to MRSM. Leaders can foster trust by prioritizing clear and transparent communication, increasing employee engagement and loyalty. The findings emphasize integrating strong leadership practices with effective communication to nurture a supportive and committed MRSM educational environment.